ENVIRONMENTAL EDUCATION IN SCHOOLS: WEAVING TOGETHER KNOWLEDGE AND PRACTICES FOR THE FORMATION OF CONSCIOUS CITIZENS THROUGH A DIDACTIC SEQUENCE - Christovão de Oliveira Lopes, Monica; de Melo Dórea, Márcia (Revista Gênero e Interdisciplinaridade, 2026)
This abstract presents a qualitative methodological intervention approach, carried out through a study group in a Municipal Daycare and Preschool in Duque de Caxias. The action took place within the scope of an extension project that aims to promote environmental education in schools, inserting and stimulating sustainable practices through lectures and discussion circles, based on applied participant observation. The description of the experience and the guiding question seeks to understand and establish Environmental Education in the school environment, investigating how teachers address these themes in their teaching practice. Using a dynamic discussion circle methodology that allowed for the exchange of experiences among participants, a questionnaire on the importance of Environmental Education was applied. The application of the questionnaire and the integrated workshops reinforced the need for an environmental theme in the school context from the earliest years of life. The study indicates the need for continuing education for teachers and the importance of discussion circles and workshops as spaces for the exchange of knowledge and the collective construction of environmental practices. In this sense, Environmental Education should be integrated transversally and critically into the daily school routine, especially in Early Childhood Education. Experience has shown that participatory methodologies are effective in promoting critical environmental education. Therefore, the continuity of participatory actions and evaluations has proven fundamental to consolidating progress and forming critical citizens committed to sustainability from the earliest school years.